2021
DOI: 10.1002/uog.22159
|View full text |Cite
|
Sign up to set email alerts
|

Fetal head progression and regression on maternal pushing at term and labor outcome

Abstract: Objectives The aim of our study was two‐fold. First, to evaluate the association between the change in the angle of progression (AoP) on maternal pushing and labor outcome. Second, to assess the incidence and clinical significance of the reduction of AoP on maternal pushing. Methods This was a prospective cohort study of nulliparous women with singleton pregnancy at term. AoP was measured at rest and on maximum Valsalva maneuver before the onset of labor, and the difference between AoP on maximum Valsalva and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A number of studies have demonstrated previously that, even when the fetal head is easily palpable, the reproducibility of digital examination of fetal head engagement is poor [41][42][43][44] . TPU provides a highly reproducible and accurate tool for fetal head descent assessment, and it has high acceptability among women due to its non-invasiveness 22,25,26,[44][45][46][47][48][49][50] . We believe that accurate assessment of fetal breech descent in the birth canal by means of BPA measurement could help in providing more accurate and applicable predictive models of ECV success, although studies are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated previously that, even when the fetal head is easily palpable, the reproducibility of digital examination of fetal head engagement is poor [41][42][43][44] . TPU provides a highly reproducible and accurate tool for fetal head descent assessment, and it has high acceptability among women due to its non-invasiveness 22,25,26,[44][45][46][47][48][49][50] . We believe that accurate assessment of fetal breech descent in the birth canal by means of BPA measurement could help in providing more accurate and applicable predictive models of ECV success, although studies are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 A very recent study showed that the change in fetal head engagement on maternal pushing as measured by TPU was associated with shorter second stage. 28 The role of the pelvic floor in the fetal engagement is not clear and we encourage future research on this topic.…”
Section: Discussionmentioning
confidence: 95%
“…Intrapartum ultrasound has been widely employed as a risk assessment tool for obstetricians to find abnormal labor courses in a noninvasive and objective way (4)(5)(6). With high accuracy, intrapartum ultrasound is a potentially predictive method for women who require OI due to failed SVD (7)(8)(9). However, short time windows in obstetric emergencies limit obstetric preparation (10).…”
Section: Introductionmentioning
confidence: 99%